Cultural values, institutions and earnings management: Evidence from a cross-country study - Yu, Yao (2020)
This study investigates how culture and institutions directly and in interaction influence the variance in earnings management in countries around the world. Using the sample of 12,500 firm-year observations and 2,500 non-financial firms across 25 countries, this study documents systematic differences in the level of earnings management across 25 countries. The findings show that both cultural values and institutional characteristics are significant in explaining a substantial portion of the variation in earnings management. Specifically, earnings management are more pervasive in countries with higher level of uncertainty avoidance, and lower level of individualism, outside investor protection and legal enforcement.